Iterative Exponential Growth of Oxygen-Linked Aromatic Polymers Driven by Nucleophilic Aromatic Substitution Reactions - Jaynes, Tyler J.; Sharafi, Mona; Campbell, Joseph P.; Bocanegra, Jessica; McKay, Kyle T.; Little, Kassondra; Osadchey Brown, Reilly; Gray, Danielle L.; Woods, Toby J.; Li, Jianing; Schneebeli, Severin T. (Frontiers in Chemistry, 2021)
This work presents the first transition metal-free synthesis of oxygen-linked aromatic polymers by integrating iterative exponential polymer growth (IEG) with nucleophilic aromatic substitution (SNAr) reactions. Our approach applies methyl sulfones as the leaving groups, which eliminates the need for a transition-metal catalyst, while also providing flexibility in functionality and configuration of the building blocks used. As indicated by (i) 1H-1H NOESY NMR spectroscopy, (ii) single crystal X-ray crystallography, and (iii) density functional theory (DFT) calculations, the unimolecular polymers obtained are folded by non-classical hydrogen bonds formed between the oxygens of the electron rich aromatic rings and the positively-polarized C–H bonds of the electron poor pyrimidine functions. Our results not only introduce a transition metal-free synthetic methodology to access precision polymers, but also demonstrate how interactions between relatively small, neutral aromatic units in the polymers can be utilized as a new supramolecular interaction pairs to control the folding of precision macromolecules.